2018
DOI: 10.7150/thno.24512
|View full text |Cite
|
Sign up to set email alerts
|

MRI and histological evaluation of pulsed focused ultrasound and microbubbles treatment effects in the brain

Abstract: Magnetic resonance imaging (MRI)-guided pulsed focused ultrasound (pFUS) combined with microbubbles (MB) contrast agent infusion has been shown to transiently disrupt the blood-brain barrier (BBBD), increasing the delivery of neurotherapeutics to treat central nervous system (CNS) diseases. pFUS interaction with the intravascular MB results in acoustic cavitation forces passing through the neurovascular unit (NVU), inducing BBBD detected on contrast-enhanced MRI. Multiple pFUS+MB exposures in Alzheimer's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 134 publications
(176 reference statements)
6
85
0
Order By: Relevance
“…Moreover, transcriptomic analysis in the acute stages following sonication revealed a transient upregulation in proinflammatory cytokines and chemokines including chemokine (C‐C motif) ligand 2, chemokine (C‐C motif) ligand 3, and Tumor necrosis factor that have been found to promote the migration, proliferation, differentiation, and survival of neural progenitor cells favoring neurogenesis . The prominent presence of Bromodeoxyuridine‐positive cells in animals that survived for a week after the last of 6 sonications has been linked to enhanced neurogenesis attributed to the expression of trophic factors such as brain‐derived neurotrophic (BDNF) in the targeted brain . Concurrent with the overexpression of inflammatory markers that mostly resolved within 24 hours was the increase in angiogenetic‐related genes and astrocytic activation …”
Section: The Bbb Opening With Fusmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, transcriptomic analysis in the acute stages following sonication revealed a transient upregulation in proinflammatory cytokines and chemokines including chemokine (C‐C motif) ligand 2, chemokine (C‐C motif) ligand 3, and Tumor necrosis factor that have been found to promote the migration, proliferation, differentiation, and survival of neural progenitor cells favoring neurogenesis . The prominent presence of Bromodeoxyuridine‐positive cells in animals that survived for a week after the last of 6 sonications has been linked to enhanced neurogenesis attributed to the expression of trophic factors such as brain‐derived neurotrophic (BDNF) in the targeted brain . Concurrent with the overexpression of inflammatory markers that mostly resolved within 24 hours was the increase in angiogenetic‐related genes and astrocytic activation …”
Section: The Bbb Opening With Fusmentioning
confidence: 99%
“…31 The prominent presence of Bromodeoxyuridine-positive cells in animals that survived for a week after the last of 6 sonications has been linked to enhanced neurogenesis attributed to the expression of trophic factors such as brain-derived neurotrophic (BDNF) in the targeted brain. 32 Concurrent with the overexpression of inflammatory markers that mostly resolved within 24 hours was the increase in angiogenetic-related genes and astrocytic activation. 31 Despite the positive impact of the technique, reports on elevated microtubule-associated protein tau, phosphorylated at the Phospho-Tau (Thr231) Monoclonal Antibody epitope 32 and activated nuclear factor kappa-light-chain-enhancer of activated Bcells (Nf-κB) pathway 33 following repeated sonications, alarmed the ultrasound field and surfaced important unmet needs.…”
Section: The Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that, under certain conditions, opening of the BBB by FUS and MBs can induce an acute sterile inflammatory response in brain tissue (58)(59)(60). The inflammation induced by FUS has been shown to promote a wide range of beneficial effects, including immune activation and recognition Significance Focused ultrasound (FUS) is a targeted and noninvasive technique that can be used to activate gas-filled microbubbles (MBs) to oscillate within the bloodstream.…”
mentioning
confidence: 99%
“…This question needs further exploration, especially if FUS might be envisioned for use repeatedly within the same brain territory. After experimental FUS, several types of tissue responses have been described, including localized edema, ischemia, hemorrhage, microglial activation, and other cellular changes lasting for up to several days afterward . A better understanding of the significance of such changes is needed to guide the safe and efficacious development of low‐energy sonication in human therapeutics.…”
Section: Perspectives: Current Situation and Future Developmentsmentioning
confidence: 99%